2022
DOI: 10.22178/pos.87-7
|View full text |Cite
|
Sign up to set email alerts
|

Organic Waste Management in the Hospitality Area for the Development and Conservation of Ecotourism in the Mandalika Special Economic Zone, Indonesia: Literature Review

Abstract: The Mandalika Special Economic Zone is included in five super Priority Travel Destinations throughout Indonesia. Mandalika has two main potential tourist attractions: the beauty of white sand and green hills along the coastline that stretches for 7.2 km. The target for Mandalika for Total Hotels & Resorts is 10,000 units, and villas, condominiums, and townhouses are 3800 units which will potentially become a source of waste. The total landfill in Mandalika is 215.7 tonnes/per year. Waste management, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…Studies have shown a shift towards recognizing informal waste workers as essential in municipal waste management (Boampong et al, 2020). Addressing equity and access involves empowering local communities, increasing community involvement in waste management, and exploring economic opportunities within waste management to boost employment (Pauzi & Purwoko, 2022). Community engagement is vital for effective waste management.…”
Section: Expected Outcomesmentioning
confidence: 99%
“…Studies have shown a shift towards recognizing informal waste workers as essential in municipal waste management (Boampong et al, 2020). Addressing equity and access involves empowering local communities, increasing community involvement in waste management, and exploring economic opportunities within waste management to boost employment (Pauzi & Purwoko, 2022). Community engagement is vital for effective waste management.…”
Section: Expected Outcomesmentioning
confidence: 99%